Isu problem dan tantangan pendidikan Islam multikultural - Yunita Wahyu Pustiadiningsih; Fery Diantoro; Muhammad Raihan Zakki Ilyasa; Vattra Putra Pratama (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2026)
This study examines the issues, problems, and challenges in the implementation of multicultural Islamic education in Indonesia. As an archipelagic nation rich in ethnic, cultural, linguistic, and religious diversity, Indonesia faces unique challenges in maintaining social harmony. Multicultural Islamic education serves as an effort to integrate inclusive Islamic values with the principles of multiculturalism to foster a generation that is tolerant and respects diversity. This study employs a qualitative descriptive method, with data collection conducted through in-depth interviews, observations, and document analysis. The findings identify several key issues, including a curriculum that is not yet fully integrated with multicultural values, teaching methods that lack adaptability, the need to improve educators’ qualifications, as well as the presence of prejudice and resistance from certain segments of society. Additionally, challenges in internalizing multicultural values arise due to students’ interactions outside of school, differences in religious understanding, family backgrounds, as well as limitations in school facilities and learning strategies. The challenges teachers face in teaching multicultural values include the diversity of students’ backgrounds, low levels of teachers’ multicultural literacy, resistance to pluralism, a lack of environmental support, limited learning strategies and media, and differences in perception among teachers. Despite facing various challenges, teachers play a strategic role in instilling these values.